Highly efficient gold-catalyzed synthesis of dibenzocycloheptatrienes - Pflästerer, Daniel; Rettenmeier, Eva; Schneider, Severin; Heras Ruiz, Edgar de las; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemistry - a European journal, 2014)
Dibenzocycloheptatrienes are obtained by a gold-catalyzed 7-exo-dig hydroarylation protocol in a highly efficient manner. The gold-catalyzed reaction usually gives the products in high yields and excellent selectivity. This procedure provides an easy and efficient access to dibenzocycloheptanoids, which are an interesting and unique class of natural products. This was underlined by the first total synthesis of reticuol.
Gesehen am 22.09.2020